Efficacy of extracts from Datura Metel L. for Psoriasis: a meta-analysis of case series and single-arm studies - Xiaopu Sang; Huanzhou Bi; Xinlei Si; Yihang Wang; Xianjie Shi; Fenfang Wu (BMC, 2023)
Abstract Background Datura Metel L. has been used to treat psoriasis in China for a long time. The effect of extracts from Datura Metel L. for Psoriasis has not been previously confirmed. This study aimed to evaluate the efficacy of extracts from Datura Metel L. for patients with psoriasis. Methods PubMed, Cochrane Library, Embase, and other databases were searched from database inception until to September 1, 2021. A quality assessment and data extraction were performed by 2 independent reviews. We used a random-effects meta-analysis model to estimate the pooled curative effect, pooled odds ratio (OR), and 95% confidence intervals. Results Nine studies were included in Meta-analysis, including a total number of 1778 patients with psoriasis. The case cure rate of Datura Metel L. intravenous therapy was 0.48 (95% CI: 0.33, 0.62) and of Datura Metel L. oral therapy was 0.42 (95% CI: 0.17, 0.68), respectively. The case effective rate of Datura Metel L. intravenous therapy was 0.91 (95% CI: 0.84, 0.97) and of Datura Metel L. oral therapy was 0.94 (95% CI: 0.88, 0.99), respectively. Conclusions The extracts from Datura Metel L. showed the potential to treat psoriasis, and intravenous therapy might be a promising treatment to cure psoriasis, which is likely affected by selection and publication bias, still need more high quality clinical studies.